THE INFLUENCE OF WORK DISCIPLINE AND INDIVIDUAL CHARACTERISTICS ON TOTAL QUALITY MANAGEMENT (STUDY AT PT. SINJARAGA SANTIKA SPORT MAJALENGKA - Fauzi, Haris (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This research is motivated by the influence of the rapid devloment of the busine world that causes very intense competition in it. This study aims to determine work discipline, individual characteristics and total quality management and to find out how much influence the work discipline and individual characteristics have on total quality management of PT. Sinjaraga Santika Sport Majalengka. This research method uses survet methods with Descriptive and Verification approaches. The sample in this study was 40 people, data samples taken from the entire population. This study uses a saturated or census sampling techniques is to spread the questionnaire. The data analysis design used Descriptive Analysis, Verification Analysis, (Classical Assumption Test, Multiple Linear Regression Analysis, Determination Coefficient Analysis and t Test). The results obtained show that employee work discipline is very high, and total quality management is very high. Partially, work discipline has a significant effect on total quality management, and individual characteristics have a significant effect on total quality management.